Assessing the benefits of anaortic off-pump coronary artery bypass grafting - Ushioda, Ryohei; Hirofuji, Aina; Yoongtong, Dit; Sakboon, Boonsap; Cheewinmethasiri, Jaroen; Lokeskrawee, Thanin; Patumanond, Jayanton; Lawanaskol, Suppachai; Kamiya, Hiroyuki; Arayawudhikul, Nuttapon (Frontiers in Cardiovascular Medicine, 2024)
Introduction The procedure called the “aorta no-touch” (NT) or anaortic technique in off-pump coronary artery bypass grafting (OPCAB) is designed to reduce the perioperative risk of stroke. We have observed an increased frequency of anaortic OPCAB procedures at our institution. The main purpose of the present study is to investigate the effectiveness of anaortic OPCAB in reducing the perioperative risk of stroke. Methods From April 2011 to July 2023, a total of 2,236 patients underwent isolated OPCAB at our single center. The patients were divided into the anaortic group (NT, n = 762) and the aortic group (A, n = 1,474). The NT group was propensity score-matched (PSM) with the A group at a 1:1 ratio (NT n = 640; A n = 640), and matching was performed based on 26 covariates with preoperative clinical characteristics. Results In both the unmatched and matched cohorts of the NT and A groups, there were no significant differences observed in new stroke rates (NT vs. A; unmatched, 1.0% vs. 1.2%, p = 0.624; matched, 0.9% vs. 1.3%, p = 0.789). The univariable logistic analysis did not identify the anaortic technique as an independent factor negatively associated with new stroke events (OR = 0.81, 95% CI = 0.35–1.86, p = 0.624). Conclusion The present study did not find the anaortic technique to reduce the perioperative risk of stroke in OPCAB. Hence, further large studies are needed to identify patient cohorts in which anaortic OPCAB is significantly beneficial.